2019
DOI: 10.4236/gep.2019.74008
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Drinking Water and Prevalence of Waterborne Diseases in the Gaza Strip, Palestine: A Narrative Review

Abstract: Water quality and occurrence of water-borne diseases in the Gaza strip are vivid examples for most developing societies. In recent years, the quality and quantity of groundwater, the only source of waters in the Gaza strip, have deteriorated markedly. A general rundown of the infrastructure and water distribution networks, in particular, the spread of cesspools, excessive use of pesticides and fertilizers, and improper treatment and disposal of wastewater remain major contributing factors to the continued dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…In our study, we reported a high prevalence of diarrhea in the Gaza strip (3.8 per 100). Factors related to this prevalence are complex in nature including but not limited to ineffective sewage management and lack access to safe drinking water [18, 19]. The epidemiological bulletin published by the UNRWA indicated a constantly increase in trend of diarrheal incidence between 2010 and 2013 [4].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we reported a high prevalence of diarrhea in the Gaza strip (3.8 per 100). Factors related to this prevalence are complex in nature including but not limited to ineffective sewage management and lack access to safe drinking water [18, 19]. The epidemiological bulletin published by the UNRWA indicated a constantly increase in trend of diarrheal incidence between 2010 and 2013 [4].…”
Section: Discussionmentioning
confidence: 99%
“… 14 16 These, in addition to many other factors, have deepened the fragility of Gaza’s health system and efforts towards universal health coverage during the COVID-19 pandemic. 17 19 …”
Section: Introductionmentioning
confidence: 99%
“…e high level of aquifer salinity was attributable to the mobilization of deep brines and seawater intrusion due to overabstraction of groundwater [32][33][34]. Several recommendations were proposed by Abbas et al and Abuzerr et al aimed to improve the quality of groundwater as well as the areas surrounding the water wells [35,36].…”
Section: Discussionmentioning
confidence: 99%